كرة السلة - كرميش، عبدالمالك فريد (University of M'sila Mohamed Boudiaf, 2021)
الملخص : المطبوعة موجهة لطلبة السنة أولى ليسانس جذع مشترك بمعهد علوم وتقنيات النشاطات البدنية والرياضية بجامعة المسيلة حيث تناولت المطبوعة في البداية لمحة تاريخية عن كرة السلة ثم قانون كرة السلة بدءا بالحكام و المهارات الأساسية و اشكال التحضير و الإعداد الرياضي ثم الانتقاء في كرة السلة ثم أسس وشروط وبرامج الانتقاء في كرة السلة و في الأخير الصفات البدنية وطرق تنميتها عند لاعبي كرة السلة الكلمات المفتاحية / كرة السلة Abstract : The publication isdirected to first-yearstudents of the commoncorebachelor'sdegreeat the Institute of Sciences and Techniques of Physical and Sports Activitiesat the University of M'sila. The publication initiallycovered a historicaloverview of basketball, then the basketball law, startingwith referees, basic skills, forms of preparation and sports preparation, thenselection in basketball, then the foundations, conditions and selection programs in basketball, and finally the physicalqualities and ways to developthem in basketball players. Keywords / Basketball
كرة السلة
Keywords: كرة السلة; المطبوعة; الإعداد الرياضي